Model Konsep Kurikulum Pendidikan : Model, Kurikulum, Pendidikan - Norjamilah (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2025)
Curriculum concept models are theoretical frameworks that serve as the foundation for planning, developing, and implementing curricula. Each model reflects a particular educational approach and influences the direction and content of learning. This study aims to examine four curriculum concept models formulated by educational experts: the academic subject model, the humanistic model, the social reconstruction model, and the technological model. This research employs a qualitative analysis method with a literature review approach, using data sourced from textbooks and scholarly journals. The findings reveal that: (1) the academic subject model emphasizes mastery of knowledge across disciplines and is rooted in traditional education; (2) the humanistic model focuses on personal development and the individual potential of students; (3) the social reconstruction model directs the curriculum toward addressing societal issues; and (4) the technological model emphasizes the integration of technology in learning to prepare students for the digital era. These four models represent different educational streams and are essential considerations for developing a contextual and future-oriented curriculum.